2008
DOI: 10.1016/j.jpsychires.2008.01.011
|View full text |Cite
|
Sign up to set email alerts
|

What explains the relation between family poverty and childhood depressive symptoms?

Abstract: The relation between low socioeconomic status (SES) and depression has been well-documented in adult populations. A number of studies suggest that family SES may be associated with depression among children and adolescents as well, although the evidence is mixed. We assessed the relation between family income and depressive symptoms among 457 children aged 11-13 years and examined pathways that may explain this relation. In-person interviews of children and their caregivers were conducted, including assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
85
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(93 citation statements)
references
References 79 publications
7
85
1
Order By: Relevance
“…Depression in poor children younger than 18 years has been linked to substance abuse, poor academic performance, teen childbearing, and unemployment. 132 Poor children also are more likely to be diagnosed with conduct disorders 133 and attentiondeficit/hyperactivity disorder. 134 Substance abuse, including alcohol and tobacco, is higher for poor adolescents, increasing the risk of emphysema and cirrhosis as well as cancer.…”
Section: Compromised Mental Health Behavioral Health and Relationalmentioning
confidence: 99%
“…Depression in poor children younger than 18 years has been linked to substance abuse, poor academic performance, teen childbearing, and unemployment. 132 Poor children also are more likely to be diagnosed with conduct disorders 133 and attentiondeficit/hyperactivity disorder. 134 Substance abuse, including alcohol and tobacco, is higher for poor adolescents, increasing the risk of emphysema and cirrhosis as well as cancer.…”
Section: Compromised Mental Health Behavioral Health and Relationalmentioning
confidence: 99%
“…Previous studies have shown that the NEO-PI-R has good reliability and validity (Costa & McCrae, 1992a;McCrae, 2011). In our study, we mainly focused on depression-related traits of the neuroticism (N3) dimension, based on the a priori hypothesis predicting a relationship between depression-related traits and family SES (Goodman et al, 2003;Tracy et al, 2008). The N3 consists of eight items, including two reverse-scored items to reduce the effects of acquiescence.…”
Section: Measuring the Level Of Depression-related Personality Traitsmentioning
confidence: 99%
“…SES-related mental health disparities have become an increasingly important and visible part of the public health landscape (Zimmerman & Katon, 2005). For example, many researchers have focused on the relationship of SES disparities with depression, and their work indicates that SES is associated with depressive symptoms and a greater likelihood of depression (Goodman, 1999;Goodman, Slap, & Huang, 2003;McLoyd, 1997;Tracy, Zimmerman, Galea, McCauley, & Stoep, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Neglect often occurs in the presence of other psychosocial risk factors, such as low socioeconomic status (SES) and exposure to violence [83][84][85]. Low SES and exposure to violence have each been associated with increased depressive symptoms in childhood [83,86,87]. Specifically, children who experience neglect may be at increased risk of experiencing shame, which in turn increases their risk for depressive symptoms [83].…”
Section: Family and Hereditary Factorsmentioning
confidence: 99%
“…The associations of being overweight and low socioeconomic status in childhood depression have been well documented [162]. Children in families of low socioeconomic status that experience family disruption or parental divorce, or that have a history of mental disorders may be at an increased risk of developing depression in later life [87,162,163].…”
Section: Comorbiditiesmentioning
confidence: 99%